Changes in baroreflex responses of kindled rats - ONAT, FİLİZ; APAYDIN KAYA, MEMNUNE ÇİĞDEM (WILEY, 2005)
Purpose: This Study was planned to investigate the baroreflex responses (BRs) in kindled rats during seizure-free period to put forward new data on cardiac autonomic changes in epilepsy. Methods: Male Wistar rats were randomized into sham-operated (SO) and kindled groups where stimulation and recording electrodes were implanted stereotaxically into the basolateral amygdala and the cortex, respectively. For kindling process, rats were stimulated twice daily at their afterdischarge threshold current and accepted as being kindled after 10 grade 5 seizures. Six to 8 weeks after the establishment of the kindled state, mean arterial pressure (MAP) and heart rate (HR) were evaluated. BR was defined as the ratio of HR response to changes in MAP induced by i.v. nitroprusside (10, 25 mu g/kg) or i.v. pherylephrine (10, 25 mu g/kg). The sympathetic or parasympathetic component of the BR was evaluated in rats pretreated with atropine or atenolol where phenylephrine or nitroprusside was administered at 25 mu g/kg. Results: Basal MAP and HR values were found to be similar in SO and kindled rats. Phenylephrine increased MAP more in the kindled group (p < 0.05), but the HR decreased similarly in both groups. Nitroprusside decreased MAP at similar rates, but the increase in HR was higher in the kindled rats (p < 0.05). BRs to phenylephrine and nitroprusside were abolished after pretreatment with atenolol and atropine, whereas pherylephrine- and nitroprusside-induced changes in MAP remained unchanged in both groups. Conclusions: These results may indicate that amygdaloid kindling affects BRs in long-term seizure-free periods.
Keywords: SUDEP; baroreflex responses; kindling; epilepsy; autonomic dysfunction; AUTONOMIC NERVOUS-SYSTEM; EPILEPTOGENIC ACTIVITY